1996
DOI: 10.1111/j.1365-2672.1996.tb03234.x
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenes in poultry and poultry products: epidemiological investigations in seven Danish abattoirs

Abstract: Listeria monocytogenes was isolated from 11/236 (4 x 7%) caecal samples from parent flocks, providing broilers to the abattoirs investigated. Caecal samples from 2078 broilers representing 90 randomly selected broiler flocks were negative for L. monocytogenes. A total of 3080 samples from seven abattoirs including poultry processing line samples, and final products were also examined for L. monocytogenes. Listeria monocytogenes was isolated in 0 x 3% to 18 x 7% of the samples collected in the different abattoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
51
0
4

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(65 citation statements)
references
References 25 publications
10
51
0
4
Order By: Relevance
“…In addition, older birds are more resistant to experimental challenge than are younger birds, the majority of which rapidly clear the infection (40). Studies conducted at a slaughterhouse indicate that contamination of turkey products occurs during processing, especially after evisceration and chilling (15,27). In addition, the Food Safety and Inspection Service microbial baseline conducted in 1995 reported L. monocytogenes in carcass washes of 15% of broilers and 5.9% of turkeys.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, older birds are more resistant to experimental challenge than are younger birds, the majority of which rapidly clear the infection (40). Studies conducted at a slaughterhouse indicate that contamination of turkey products occurs during processing, especially after evisceration and chilling (15,27). In addition, the Food Safety and Inspection Service microbial baseline conducted in 1995 reported L. monocytogenes in carcass washes of 15% of broilers and 5.9% of turkeys.…”
Section: Discussionmentioning
confidence: 99%
“…Carriage estimates for live chickens, based on cecal samples from parent breeders (4.7%) and 2,078 broilers (0%) (27) as well as broiler ock surveys (3% of 71 ocks were positive) (28), indicate that L. monocytogenes is infrequently found in live adult birds. In addition, older birds are more resistant to experimental challenge than are younger birds, the majority of which rapidly clear the infection (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2) has been obtained from only two available primary studies (Antunes et al, 2002;Mena et al, 2004), at present the main recommendation can be for enabling actions to address the data gap. Djeniyi, Wegener, Jensen, and Bisgaard (1996) indicated that because L. monocytogenes is not frequently isolated from chickens, it is likely that the live animals may only contribute little to the total contamination of the abattoir, and that the pathogen may be introduced from dirty transport crates. Even though, poultry has not been associated to a great extent with human listeriosis, variable incidence rates of this pathogen have been found in the past in Denmark (23%; Djeniyi et al, 1996), USA (30%; Cox, Bailey, & Berrang, 1997), Ireland (6-30%;Whyte, McGill, Monahan, & Collins, 2004), Northern Ireland (17%; Soultos, Koidis, & Madden, 2003) and Brazil (28%; Loura, Almeida, & Almeida, 2005).…”
Section: Tablementioning
confidence: 99%
“…Djeniyi, Wegener, Jensen, and Bisgaard (1996) indicated that because L. monocytogenes is not frequently isolated from chickens, it is likely that the live animals may only contribute little to the total contamination of the abattoir, and that the pathogen may be introduced from dirty transport crates. Even though, poultry has not been associated to a great extent with human listeriosis, variable incidence rates of this pathogen have been found in the past in Denmark (23%; Djeniyi et al, 1996), USA (30%; Cox, Bailey, & Berrang, 1997), Ireland (6-30%;Whyte, McGill, Monahan, & Collins, 2004), Northern Ireland (17%; Soultos, Koidis, & Madden, 2003) and Brazil (28%; Loura, Almeida, & Almeida, 2005). Thus, these and the Portuguese results highlight that the presence of L. monocytogenes in Portuguese broiler meat would not be uncommon; and hence, maintaining good hygiene practices in production, processing and the consumer's kitchen cannot be overemphasized.…”
Section: Tablementioning
confidence: 99%